The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1099/vir.0.80110-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of central nervous system genes involved in the host response to the scrapie agent during preclinical and clinical infection

Abstract: Genes that are expressed differentially in the central nervous system of mice during infection with mouse-adapted scrapie agents were identified in this study. cDNA microarrays were used to examine gene-expression profiles at early, middle (preclinical) and late (clinical) time points after inoculation. A number of genes that showed significant changes in expression during the clinical stage of disease were identified. Of these, 138 were upregulated and 20 were downregulated. A smaller number of genes showed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
2
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 32 publications
7
84
2
10
Order By: Relevance
“…Various high-throughput techniques, such as microarray expression profiling (11)(12)(13)(14)(15)(16)(17)(18)(19) and quantitative bead-based suspension array systems (3,20,21), have allowed elucidation of transcriptional and protein changes in brains of prion-infected mice relative to controls. These studies supported the notion that prion diseases have a neuroinflammatory component that may play a critical role in neurodegeneration (22), with increases in numerous cytokines and chemokines, such as interleukin-1␣ (IL-1␣) and IL-1␤, IL-12p40, tumor necrosis factor (TNF), CCL2 to CCL6, and CXCL10 in the brains of mice with clinical disease.…”
mentioning
confidence: 99%
“…Various high-throughput techniques, such as microarray expression profiling (11)(12)(13)(14)(15)(16)(17)(18)(19) and quantitative bead-based suspension array systems (3,20,21), have allowed elucidation of transcriptional and protein changes in brains of prion-infected mice relative to controls. These studies supported the notion that prion diseases have a neuroinflammatory component that may play a critical role in neurodegeneration (22), with increases in numerous cytokines and chemokines, such as interleukin-1␣ (IL-1␣) and IL-1␤, IL-12p40, tumor necrosis factor (TNF), CCL2 to CCL6, and CXCL10 in the brains of mice with clinical disease.…”
mentioning
confidence: 99%
“…The correlation between BSE pathogenesis and the transcriptional activities of genes is however not explored in any detail. Gene expression profiling studies of mice with scrapie have shown that these studies can provide valuable insights in the possible pathomechanisms of the disease (5,25,27,29,36,37).…”
mentioning
confidence: 99%
“…As noted, some of the most prominent incipient prion-related changes from whole tissue analyses (i.e., inflammation, cell adhesion, cell proliferation, energy metabolism, pattern recognition receptors and leukocyte extravasation) [27][28][29][30][64][65][66] were largely absent from the microdissected neuronal material or relegated to the later time-points when disease coincided with the significant infiltration of immune cells into the dissection field. This means that we can start to differentiate between temporal changes in neurons and the interplay with other cells that make up the brain tissue milieu.…”
Section: Preclinical Ca1 Microrna Profilesmentioning
confidence: 99%